The Impact of Health Counseling on Parental Behavior in Preventing Diarrhea in Toddlers in Keluas Hulu Village, 2024** - Wardi; Sohibun, Sohibun; Nurul Khoirunnisa (Jurnal Surya, 2024)
Introduction: Several diseases closely related to environmental sanitation remain persistent health issues in society, one of which is diarrhea. This is evidenced by the high number of diarrhea cases, particularly among toddlers, visiting healthcare facilities. This study aims to determine the impact of health education on parental behavior in preventing diarrhea in toddlers in Keluas Hulu Village. Methods: This research uses a quantitative method with a pre-experimental design and employs a One Group Pretest-Posttest Design. The population consisted of 101 individuals, with a sample size of 43 mothers of toddlers. The data were tested using Wilcoxon test. Results: Afer giving the health education, mean score of knowledge was increased from 7.1 to 8.5 (P-value = 0.000). Mean score of attitude was increased from 31.1 to 31.9 (P-value = 0.002). Mean score of practice was increased from 5.2 to 5.6  (P-value = 0.043). Conclusion Health education significantly impacts parental behavior in preventing diarrhea in toddlers in Keluas Hulu Village, the working area of Ulak Muid Community Health Center, Melawi Regency Keywords: Attitude, Behavior, Diarrhea, Knowledge, Health education